Instillation Anesthesia in Refractive Surgery in Children - A. G. Shchuko; L. C. Khlebnikova; I. G. Oleshenko; T. N. Iureva; O. V. Pisarevskaya; T. N. Frolova (Oftalʹmologiâ)
Purpose: to evaluate the safety and clinical efficacy of the Femto-LASIK refractive surgery performed under local (topical) anesthesia in children and adolescents with anisometropic and refractive amblyopia against a background of mixed astigmatism, medium and high hypermetropia with hypermetropic astigmatism.Patients and methods: 28 children (28 eyes) aged from 7 to 16 years (av. age — 13.6 ± 2.1 years old) were operated under local anesthesia by the FemtoLASIK method. The degree of anisometropy was from 3.25 to 5.21 (average — 4.27 ± 0.53 D). Uncorrected visual acuity averaged 0.21 ± 0.07, corrected one — 0.41 ± 0.1. Psychological history of patients and readiness for operative treatment of the disease were found out during the diagnostic examination. Based on the Spielberger-Khanin technique, the level of personal and reactive anxiety was determined, allowing identifying patients for surgical intervention under topical anesthesia. The surgeon assessed the comfort of the operation. During the first postoperative examination, the developed questionnaire was used to assess the comfort level of the patient during surgical treatment.Results. During the surgical intervention and in the postoperative period there were no complications. The behavior of all patients during the operation can be considered adequate. The duration of the operation slightly exceeded the duration of FemtoLASIC in adults. Uncorrected visual acuity in the first day after the operation averaged 0.39 ± 0.08, in 6 months — 0.61 ± 0.1, which is 80% higher than the baseline indices. After 6 months, the equivalent of anisometropia was 0.69 ± 0.12 D, that is, the refraction of the operated eye approached the value of the paired eye. In 60.8% of patients, the sensations during the operation corresponded to the level of “comfortable”. The surgeon’s assessment of the conditions for performing operations as ‘satisfactory” was noted in 92.9%.Conclusion. The use of topical anesthesia in refractive surgery in children with an initially low level of anxiety is an effective, safe and predictable method of anesthesia, allowing to conduct surgery in comfortable conditions for both the patient and the surgeon, with a high functional result.